(untitled) (NAU Journal of Technology and Vocational Education, 2025)
Due to the impact of manual functions, business education is confronted with previously unheard-of opportunities and challenges. Additionally, graduates of business education are under more pressure to find employment. The labour market has tightened its standards for workers as because of the development of artificial intelligence, and graduates with a high level of professionalism and comprehensiveness will be chosen. Consequently, as a department of business education It should accurately comprehend the artificial intelligence trend, place a high value on its impact and role in the advancement of business education, link AI to the innovation and reform of vocational education, and employ AI teaching strategies in a way that is both logical and scientific. In keeping with the advancement of the times, it is employed in everyday education to develop exceptional abilities for the nation and society. In an effort to raise the caliber of instruction and standard of business education, this article will examine how artificial intelligence is affecting vocational education and potential solutions. This study concludes that AI holds significant potential to improve the quality of business education and align it with global standards, but its benefits can only be maximized through balanced integration with traditional teaching methods. It is recommended that Institutions should encourage continuous professional development in AI applications for business educators. Also, policies that emphasize ethical and responsible AI use should also be implemented. By addressing these gaps, AI can serve as a catalyst for innovative reforms in business education and produce globally competitive graduates.